Effects of different geometric structures on fluid flow and heat transfer performance in microchannel heat sinks. (January 2015) - Xia, G.D.; Jiang, J.; Wang, J.; Zhai, Y.L.; Ma, D.D.
Abstract: In the present study, fluid flow and heat transfer in microchannel heat sinks with different inlet/outlet locations (I, C and Z-type), header shapes (triangular, trapezoidal and rectangular) and microchannel cross-section shapes (the conventional rectangular microchannel, the microchannel with offset fan-shaped reentrant cavities and the microchannel with triangular reentrant cavities) are numerically studied with computational domain including the entire microchannel heat sink. Detailed three-dimensional numerical simulations are useful in identifying the optimal geometric parameters that provide better heat transfer and flow distribution in a microchannel heat sink. Results highlight that flow velocity uniformity is comparatively better for I-type and poor for Z-type. The flow distribution is found to be symmetrical for I-type. It is seen from the header shapes analysis that the rectangular header shapes provides better flow velocity uniformity than the trapezoidal and triangular headers. The fluid flow mechanism can be attributed to the interaction of the branching of fluid and the friction offered by the walls of the header. Effects of microchannel cross-section shapes emphasize that the microchannel with offset fan-shaped reentrant cavities and the microchannel with triangular reentrant cavities of the heat sinks enhance the heat transfer compared to the conventional rectangular microchannel. The heat transfer mechanism can be attributed to the jetting and throttling effect, the additional flow disturbance near the wall of the reentrant cavities and the form drag of the reentrant cavities. The heat sink C has better heat transfer characteristic for qv  = 150 ml/min and is able to prolong the life of the microelectronic devices.